Normal left atrial diameter is associated with better performance on a cognitive screener among a cohort of ischemic stroke patients - Gootee, Emma; Stein, Colin; Walker, Alex; Daneshvari, Nicholas O.; Blaha, Michael J.; Lima, Joao A. C.; Gottesman, Rebecca F.; Johansen, Michelle C. (Frontiers in Neurology, 2022)
Background: Cardiac structure is an important determinant of ischemic stroke (IS) etiology; however, whether an association between cardiac structural markers and cognition post-IS exists is not yet established. The aim of this study is to examine the association between LAD and LVEF with cognitive performance among IS patients. Methods: IS patients admitted to the Johns Hopkins Hospital (2017-2019) underwent transthoracic echocardiography. IS was classified (TOAST) by a masked reviewer. Left atrial diameter (LAD) was evaluated as a nonlinear continuous variable with one spline knot at 4 cm; left ventricle ejection fraction (LVEF) was dichotomized, then further evaluated as a nonlinear continuous variable with spline knots at 50% and 70%. Patients were contacted by telephone on average 422 days post-stroke and administered the Six-Item Screener (SIS) to assess for dementia. SIS scores were dichotomized into low and high, imputing low scores for non-answerers. Multivariable logistic regression determined the association of SIS category with LAD or LVEF. A sensitivity analysis re-evaluated the association between SIS category and LAD, excluding participants with atrial fibrillation (AF). Results: Participants (N=108) were on average 61 years old (range=18-89 years), 55% male, and 63% Black. Among patients considered to have a normal LAD (≤4 cm), a 1 mm larger LAD was associated with 1.20 greater odds (95%CI=1.05-1.38) of scoring in the high SIS category in the final adjustment model. This association remained significant when excluding participants with prevalent AF. There was no association between a 1 mm larger LAD and SIS category among patients with a LAD >4 cm in both the primary analysis and the sensitivity analysis. There was no association between LVEF and SIS category. Conclusions: In this prospective study, among ischemic stroke patients with a LAD within the normal range, a 1 mm increase in LAD was associated with higher scores on a telephone cognitive battery, without an association found among those with a LAD >4 cm.